Small-signal model and control approach for a dual input boost converter with VMC. Issue 6 (3rd June 2022) - Appikonda, Mohan; Dhanalakshmi, K.
ABSTRACT: The dual-input boost converter (DIBC) with voltage multiplier cell (VMC) and operating in continuous conduction mode (CCM) is feasible for applications with high voltage from low voltage renewable energy sources (RES). To achieve a high voltage gain, DIBC is operated with two VMC, and overlapping switch signals, i.e. at duty ratio higher than 0.5; these complicate the modelling and control design. The objective here is to achieve output voltage regulation under load and input voltage disturbances with the proposed feed-forward plus feedback (FFFB) control strategy for DIBC with two VMC. Nevanlinna–Pick interpolation method and MATLAB SISOtool are used to design the optimally stable feed-forward controller and feedback controller, respectively. The study of the non-minimum phase behaviour of the converter, followed by the control design, is done based on the derived averaged state-space small-signal transfer function models. The analytical model is validated using MATLAB and PSIM software and experimentally. A converter prototype of 250 W is built and experimentally tested; the control is realised using FPGA. The simulation and experimental results ensure that the converter with this proposed control design provides satisfactory voltage regulation.